Phytotoxicity evaluation and phytochemical analysis of three medicinally important plants from Pakistan. (May 2015) - Ullah, Nazif; Haq, Ihsan-ul; Mirza, Bushra
This work examines the crude methanolic extracts of three medicinally important plants native to Pakistan for potent phytotoxic activities and important phytochemicals. These plants include Euphorbia wallichii, Bergenia ciliata and Phytolacca latbenia . The phytotoxic effects were checked at 10, 000, 1000, and 100 µg/ml against two economically important standard target species, Triticum aestivum (monocot representative) and Brassica napus (dicot representative). The phytotoxicity effects on seed germination, seedling growth and seedling weight were checked. A simple, cost-effective in vitro phytotoxicity assay (that uses petri plates) was used to evaluate the allelopathic properties of crude extracts. At highest concentration, extracts from all the three plants showed phytotoxic activities such that P. latbenia > E. wallichii > B. ciliata . In seedling growth, root length was affected more than shoot length, whereas among the target species B. napus was found to be more sensitive towards extracts when compared with T. aestivum . Phytochemical analysis showed that P. latbenia is rich in saponins and terpenoids, while E. wallichii and B. ciliata are rich in tannins, terpenoids and cardiac glycoside. P. latbenia also carries a moderate amount of cardiac glycosides.